2006
DOI: 10.1186/1471-2458-6-302
|View full text |Cite
|
Sign up to set email alerts
|

Municipal mortality due to thyroid cancer in Spain

Abstract: Background: Thyroid cancer is a tumor with a low but growing incidence in Spain. This study sought to depict its spatial municipal mortality pattern, using the classic model proposed by Besag, York and Mollié.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
4
8
0
1
Order By: Relevance
“…Indeed, mortality is higher in the group of women, which corroborates findings reported nationally and internationally (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). This does not mean that thyroid cancer among men is presented as a problem of lower order.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, mortality is higher in the group of women, which corroborates findings reported nationally and internationally (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). This does not mean that thyroid cancer among men is presented as a problem of lower order.…”
Section: Discussionsupporting
confidence: 82%
“…It declined in the Midwest, showing regional differences. Similar results were observed in Spain (30), where it was also shown that the distribution of thyroid cancer across the country is uneven, with the highest densities in incidence in the Canary Islands, in the province of Lugo, east of La Coruña, and in the western parts of Asturias and Orense.…”
Section: Discussionsupporting
confidence: 81%
“…The trend of decrease was significant for both sexes, although the decrease occurred earlier and was more accentuated among women. Other studies have reported results that are similar to ours for women (24)(25)(26) yet different for men (8,25,26). The decrease in mortality among women has been attributed to increasing diagnostic scrutiny (24); thus, the slighter (24) decrease among men could in part be explained by lesser access for men to analogous clinical controls.…”
Section: -2005) (12)supporting
confidence: 76%
“…In a study in which data from 12 case-control studies conducted in the United States, Asia, and Europe were pooled, a history of goiter was associated with an excess risk of nonmedullary TC (9). In Spain, TC mortality has been shown to be higher in areas that had been traditionally endemic for goiter (8). Moreover, a striking difference in the relative prevalence in the TC histotypes was reported in two adjacent areas of Sicily with different iodine intake indicating that even moderate iodine deficiency is associated with an increased frequency of more aggressive histological subtypes of TC (34).…”
Section: -2005) (12)mentioning
confidence: 99%
See 1 more Smart Citation